2017
DOI: 10.1111/1756-185x.13104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sleep disturbances in patients with familial Mediterranean fever and the relation of sleep quality with disease activity

Abstract: Poor sleep quality is common in adult FMF patients. Anxiety, depression and fatigue are more frequent in FMF patients than healthy individuals. Poor sleep quality is associated with inflammatory marker levels during attacks, fatigue and attack numbers in the last 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…1,2,9 In previous studies, a higher frequency of anxiety and depression in FMF patients has been reported. 3,5,8 In accordance with these results, we also detected a higher frequency of anxiety and depression using the subscales of HADS. In correlation analysis, we also showed a positive correlation between the FMF-QoL Scale score and HADS scores.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1,2,9 In previous studies, a higher frequency of anxiety and depression in FMF patients has been reported. 3,5,8 In accordance with these results, we also detected a higher frequency of anxiety and depression using the subscales of HADS. In correlation analysis, we also showed a positive correlation between the FMF-QoL Scale score and HADS scores.…”
Section: Discussionsupporting
confidence: 89%
“…1,2 It is a lifelong disease with harmful effects on all aspects of quality of life (QoL) due to the presence of recurrent attacks and side effects of medical treatment. 3 The concept of health-related QoL is known as the measurement of physical symptoms, functional status, and effects of the disease on psychological and social functioning. 2 As in other chronic diseases, the problems in relation to QoL for FMF patients have become an important health topic particularly during the last decades.…”
Section: Familialmentioning
confidence: 99%
“…In a study on adult patients with FMF, it was shown that FMF patients have a worse sleep pattern compared to healthy individuals. 25 Another study with children with FMF indicated higher total sleeping scores, sleep onset delay, sleep anxiety, nightwakings and sleep-disordered breathing scores in patients with FMF compared to healthy peers. 13 Similarly, in our study, total sleep score, nightwakings and sleep-disordered breathing scores were higher in patients, while sleep onset delay and sleep anxiety scores were similar; but unlike previous studies, bedtime resistance and parasomnia scores were significantly higher in patients.…”
Section: Discussionmentioning
confidence: 96%
“…In a study on adult patients with FMF, it was shown that FMF patients have a worse sleep pattern compared to healthy individuals 25 . Another study with children with FMF indicated higher total sleeping scores, sleep onset delay, sleep anxiety, nightwakings and sleep‐disordered breathing scores in patients with FMF compared to healthy peers 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation